(untitled) (Journal of Plant Disease Sciences, 2021)
Citrus canker incited by Xanthomonas citri subsp. citri is the devastating economically important bacterial diseases of Acid lime. In laboratory conditions eleven botanicals and certain chemical toxicants tested to determine their ability to control X. citri pv. citri. Among the botanicals, Azadirachta indica, Prospis juliflora, Nigella sativa, Pongamia pinnata, Ricinus communis and Eucalyptus spp, @ 10% only inhibits the growth of bacterium. Significantly highest inhibition zone (9.33 mm) recorded in Azadirachta indica leaves extract followed by Prospis juliflora (7.00 mm), Nigella sativa (5.00 mm), and Pongamia pinnata (4.66 mm). Results in respect of chemical toxicants, Streptocycline + copper oxychloride were significantly showed highest (27.66 mm) inhibition zone. Next in order of merit was treatment Streptocycline (22.00 mm) and Kasugamycine 5% + Copper oxychloride 45% (18.66 mm). Lowest inhibition zone was found in treatment Potassium Phosphonate (6.66 mm).